Determination of receptor protein binding site specificity and relative binding strength using a time-resolved competition assay - Barta, Pavel; Volkova, Marie; Dascalu, Adrian; Spiegelberg, Diana; Trejtnar, Frantisek; Andersson, Karl (Journal of pharmacological and toxicological methods, 2014)
INTRODUCTION: Competitive binding assays can be used to decipher not only the binding kinetics of studied ligands but also the binding site preference. Such assays are an essential step in the characterization of radioligands. However, the currently used competition assays require high concentrations of usually expensive ligands and still provide only binding site preference. By employing the time-resolved competition assay presented in this paper, binding characteristics including binding site preference can be obtained using less ligand. METHODS: To demonstrate the appropriateness of the time-resolved competition assay, we developed an assay in which the ligand binding was interrupted with a competitor. Experiments were performed on human carcinoma cell lines expressing epidermal growth factor receptor (EGFR). The targeting of the receptor was performed with radio-iodinated epidermal growth factor (EGF). The employed competitors involved either natural ligand transforming growth factor alpha (TGF-α) or anti-EGFR antibodies cetuximab and panitumumab targeting the same EGFR domain. RESULTS: Radio-iodinated EGF bound to EGFR was displaced with either low concentrations of cetuximab or high concentrations of panitumumab. In the case of TGF-α, we observed no competitive displacement of bound EGF at either high or low concentrations. When comparing the time-resolved competition assay with a manual competition assay, the resulting data of measured inhibition constants were in agreement. DISCUSSION: The results summarised in this study confirm the appropriateness of the time-resolved competition assay for assessing ligand binding properties. The assay has the potential to complement or replace conventional competition assays for determining binding site preference in the future.
Keywords: Transforming Growth Factor alpha; Binding, Competitive; monoklonální protilátky; ligandy; Structure-Activity Relationship; Ligands; vztah mezi dávkou a účinkem léčiva; Epidermal Growth Factor; kompetitivní vazba; vztahy mezi strukturou a aktivitou; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Time Factors; substrátová specifita; lidé; transformující růstový faktor alfa; Humans; Substrate Specificity; časové faktory; nádorové buňky kultivované; Tumor Cells, Cultured; Antibodies, Monoclonal; Dose-Response Relationship, Drug; erbB receptory; ErbB Receptors; epidermální růstový faktor